2015
DOI: 10.1038/ejcn.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

Muscle function-dependent sarcopenia and cut-off values of possible predictors in community-dwelling Turkish elderly: calf circumference, midarm muscle circumference and walking speed

Abstract: An adequate muscle mass may not mean a reliable muscle function. Muscle function may describe sarcopenia better compared with muscle mass. The CC, MAMC and 4 m WS cut-offs may be used to assess sarcopenia in certain age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 16 publications
2
38
3
2
Order By: Relevance
“…Loss of lean muscle mass and increase in fat mass contributed to lower HGS [29]. On the other hand, CC was associated with HGS univariately, but not in the multivariate model, contradicting with other study [30]. Further research is required on these aspects.…”
Section: Discussioncontrasting
confidence: 63%
“…Loss of lean muscle mass and increase in fat mass contributed to lower HGS [29]. On the other hand, CC was associated with HGS univariately, but not in the multivariate model, contradicting with other study [30]. Further research is required on these aspects.…”
Section: Discussioncontrasting
confidence: 63%
“…However, all these imaging technologies and equipment (DXA, CT and MRI) are not portable, which is important in large epidemiological studies in populations. Therefore, more research is needed to define sarcopenia and SO using other traditional or modern technologies that are safe, inexpensive and widely available including anthropometry (e.g., midupper arm or calf circumference) [38,39], bioelectrical impedance analysis (BIA) [40] and ultrasound [37]. …”
Section: Assessment and Definition Of Sarcopenic Obesitymentioning
confidence: 99%
“…A recent systematic review identified several domains of malnutrition: demographic characteristics, financial characteristics, food and appetite, lifestyle, psychological characteristics, physical functioning, disease and care, oral health, and social factors [14]. Previous studies have identified additional potential risk factors of malnutrition related to the above domains: advanced age, female and single/widowed/divorced [15, 16], low education level [17], poverty [17, 18], loss of appetite, food allergies and eating/swallowing/tasting difficulties, [12, 19, 20], cigarette smoking and alcohol consumption [21, 22], betel nut chewing [23], lack of interest, low mood, frequent negative thoughts, loneliness, depression, dementia and low cognition [17, 24], physical inactivity [12], diseases [11], tooth loss and not wearing dentures [25] and social factors such as living alone [26]. …”
Section: Introductionmentioning
confidence: 99%